Comparative assessment of nutritional composition, phenolic compounds, antioxidative and antidiabetic properties of pilosocereus gounellei and Cereus Jamacaru: two unexplored cactus fruits from the Brazilian semi-arid - Fábio Fernandes de Araújo; David de Paulo Farias; Thisun Ranpatabendi; Iramaia Angélica Neri-Numa; Glaucia Maria Pastore; Alexandra Christine Helena Frankland Sawaya (CyTA - Journal of Food)
In this study, we determine the chemical composition, bioactive compounds profile, antioxidant capacity and antidiabetic potential of two cactus fruits. Pilosocereus gounellei had the highest contents of ash (6.84%), lipid (7.79%), maltose (1.02 mg g−1), soluble fiber (10.85%) and minerals such as Mg. Thirteen volatile compounds (alcohols, terpenes, aldehydes and esters) were found in the fruits. Although higher amounts of quinic acid and quercetrin were found in Cereus Jamacaru, Pilosocereus gounellei had a higher content of p-coumaric acid and rutin. Regarding the functional potential, Cereus Jamacaru had the highest content of total phenolics (65.17 GAE g−1), total flavonoids (26.06 mg EC g−1), antioxidant capacity (28.67; 49.86; 158.79 µM TE g−1 for DPPH, ABTS and ORAC, respectively) and highest inhibition for α-amylase (84.84 ± 0.41%) and protein glycation. In view of their nutritional and bioactive characteristics, these species have great potential to be used in preparations with functional claims.